How can we improve the interpretation of systematic reviews? - Tricco, Andrea C; Straus, Sharon E; Moher, David (Université d'Ottawa | University of Ottawa, 2011)
Abstract A study conducted by Lai and colleagues, published this week in BMC Medicine, suggests that more guidance might be required for interpreting systematic review (SR) results. In the study by Lai and colleagues, positive (or favorable) results were influential in changing participants' prior beliefs about the interventions presented in the systematic review. Other studies have examined the relationship between favorable systematic review results and the publication of systematic reviews. An international registry may decrease the number of unpublished systematic reviews and will hopefully decrease redundancy, increase transparency, and increase collaboration within the SR community. In addition, using guidance from the Preferred Items for Systematic Reviews and Meta-analyses (PRISMA: http://www.prisma-statement.org/) Statement and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE: http://www.gradeworkinggroup.org/) approach can also be used to improve the interpretation of systematic reviews. In this commentary, we highlight important methodological issues related to the conduct and reporting of systematic reviews and also present our own guidance on interpreting systematic reviews. Please see Research article: http://www.biomedcentral.com/1741-7015/9/30/.